1984
DOI: 10.1080/09670878409370869
|View full text |Cite
|
Sign up to set email alerts
|

Food Preference in the Nile RatArvicanthis niloticus

Abstract: Individually tested Nile rats, Arvicanthis niloticus Desm., consistently preferred sorghum to wheat, groundnuts and standard laboratory food, and whole sorghum to cracked and ground sorghum. The addition of 5% sugar enhanced their consumption of sorghum bait. Similar results were obtained with groups of 2-4 animals in enclosures. Whole sorghum to which 2% by weight groundnut oil and 5% sugar had been added was preferred over all other foods. Small groups of rats in four enclosures were exposed to 0.18% zinc ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In addition, the Nile rat has ample exercise in wild. Due to food being a limited resource and increased exercise (as a consequence of avoiding predation and searching for food), the Nile rat in the wild does not develop diabetes when consuming a fiber-rich, low GLoad diet based on native grasses and bushes in its semi-arid desert environment [55,56,57,58].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Nile rat has ample exercise in wild. Due to food being a limited resource and increased exercise (as a consequence of avoiding predation and searching for food), the Nile rat in the wild does not develop diabetes when consuming a fiber-rich, low GLoad diet based on native grasses and bushes in its semi-arid desert environment [55,56,57,58].…”
Section: Methodsmentioning
confidence: 99%
“…Soni et al (1980) found that neither sugar nor vegetable oils enhanced bait consumption in Funambulus pennanti (northern palm squirrel) in India. However, both sugar and vegetable oil were found to enhance bait consumption in Rattus meltada (soft-furred field rat) in India (Chopra et al, 1984) and Arvicanthis niloticus (Nile rat) in Egypt (Suliman et al, 1984).…”
Section: Sugar and Other Sweetening Agentsmentioning
confidence: 99%
“…The Nile rat ( Arvicanthis niloticus ) is a model of type 2 diabetes with key benefits over other rodent models. First, diabetes is rapidly induced in both sexes by conventional laboratory rodent chow that is hypercaloric for the Nile rat compared to its native fiber-rich diet 2 , 3 . On conventional rodent chow, the onset of diabetes can range from a month to a year of age, and by 6 months of age, most of the Nile rats would have developed diabetes 4 .…”
Section: Mainmentioning
confidence: 99%